Selecting the most effective plant growth-promoting bacteria from oil palm (Elaeis guineensis Jacq) roots: Plant growth-promoting bacteria from oil palm (Journal of the Bangladesh Agricultural University, 2019)
A total of 30 bacterial isolates were isolated from soil, rhizoplane, and internal tissue of oil palm roots. The isolates were qualitatively tested for their potential to fix N2, solubilize inorganic P and K, and produce phytohormone indole-3-acetic acid. Of the 30 isolates, six isolates were able to exhibit multiple beneficial traits. All six isolates were then identified based on fatty acid methyl esters profile as Escherichia coli strain EX2, Serratia sp. strain EN1, Pantoea ananatis strain EN3, Bacillus sp. strain EN5, Pantoea ananatis strain EN8 and Pantoea sp. strain EN9. Subsequently, all shortlisted isolates were evaluated for plant growth-promoting potential by using shallot as a test plant. The plant test showed no significant difference (p>0.05) between inoculated and uninoculated plants except for Pantoea sp. strain EN9 inoculation which increased significantly (p